Physics with many positrons = Fisica con molti positroni : proceedings of the International School of Physics "Enrico Fermi" : course CLXXIV : Varenna on Lake Como, Villa Monastero 7-17 July 2009 - Dupasquier, A. (Alfredo); Mills, Allen P.; Brusa, R. S. (IOS Press, 2010)
With the exception of positron emission tomography (PET), the field of low energy positron science produces relatively few academic articles each year compared to more accessible fields. Though much has been achieved since the publication of two related volumes earlier in this series: Positron Solid State Physics (1981) and Positron Spectroscopy of Solids (1993), only the first steps have been made towards 'physics with many positrons': physical situations where the interactions of positrons with positrons can be observed. This 2009 "Enrico Fermi School" aims to stimulate the field o.